Estimation of enhanced design base shear requirement for RC buildings designed as per IS: 1893–1966, 1984 by seismic coefficient method - Raju, K. Rama; Cinitha, A.; Kamatchi, P.; Iyer, Nagesh. R.; Lakshmanan, N. (Journal of Structural Engineering, 2025)
The existing low/medium-rise buildings designed as per the old codes of practice are required to be retrofitted to comply with the base shear requirement of present seismic code (IS: 1893–2002). This paper gives an estimate of the additional shear required for three typical buildings designed prior to the present seismic code IS:1893–2002 based on the seismic zone and site soil condition of building, the importance factors to be considered based on functional requirement of the building and the type of frame chosen in design phase of the building. This additional base shear estimated need to be considered while taking retrofitting measures. For finding the additional base shear requirement, this paper reviews the three revisions of codes viz. IS: 1893–1966, 1984 and 2002 using seismic coefficient method. It is found from the analysis, the base shear demand of the buildings designed as per old versions of seismic codes IS:1893–1966, 1984 are such that they need varying degrees of retrofitting.